Omnichannel Strategies in Retail Marketing: A PRISMA-Based Systematic Literature Review and Bibliometric Analysis - Toto Heru Dwihandoko (Takuana: Jurnal Pendidikan, Sains, dan Humaniora, 2026)
This study aims to map and synthesize the development of research on omnichannel strategies in retail marketing. The research was undertaken to address the fragmented nature of existing studies, which predominantly focus on customer outcomes while overlooking organizational enablers. A PRISMA-based systematic literature review, combined with a bibliometric analysis, was employed to ensure a rigorous, transparent, and replicable approach. Following a structured screening process, 70 relevant empirical articles published between 2020 and 2025 were analyzed to identify publication trends, dominant themes, and research gaps. The findings indicate that omnichannel research has grown rapidly and is strongly centered on customer experience, satisfaction, loyalty, and behavioral intentions, reflecting the prominence of Customer Journey Theory. However, limited attention is given to internal organisational capabilities. By integrating the Resource-Based View, this study highlights the importance of coordinated internal resources for effective omnichannel implementation and provides directions for future research and managerial practice.